Is the thesis of Christ’s beatific vision defensible today? - Gaine, S (Pontifical University of St. Thomas Aquinas, 2017)
The publication of my recent book, Did the Saviour See the Father? Christ, Salvation and the Vision of God, led to me being asked to speak about the contemporary defensibility of the thesis of Christ’s beatific knowledge. To illustrate something of the defensibility of the thesis, I spoke about how and why I came to write the book, and how and why I came to write it the way I did. I was initially motivated to write on the topic because it was controversial. From unanimity in favour of Christ’s beatific vision among Catholic theologians in the first half of the twentieth century, there was a shift to a similar consensus against the thesis in the second half of the century. My book deals with reasons standardly given against the thesis, behind which is a general feeling that it makes Christ’s humanity somehow unreal, including objections based on limitations in Christ’s knowledge, his freedom, and suffering. Two objections which surprised me by their significance were the lack of biblical evidence and the idea that Christ had faith, both of which influenced the shape of the argument of my book in unexpected ways. I conclude that there has been a shift in what is required to defend the thesis of Christ’s beatific vision, from arguing against the view that it makes Christ’s humanity unreal, to arguing against the view that it makes him exceptional, to arguing against the view that Christ had faith.